Spatial Analysis and Mapping of Highly Pathogenic Avian Inﬂ uenza in Thailand Using National Outbreak Data: An Area-Based Risk Orientation - Poolkhet, Chaithep; Chairatanayuth, Pornsri; Thongratsakul, Sukanya; Thanapongthum, Weerapong; Rakkwamsuk, Theera (Agriculture and Natural Resources, 2012)
Highly pathogenic avian inﬂ uenza (HPAI) H5N1 is an infectious disease that can be transmitted from animals to humans. The disease is widely spread throughout the world, including Thailand. Many researchers have studied the risk factors associated with the presence of H5N1 and spatial techniques are commonly used for evaluation. The present study investigated outbreaks of HPAI H5N1 in Thailand between January 2004 and November 2005 using kernel smoothing and Kulldorff’s scan statistics. A total of 1,493 HPAI H5N1 outbreak points from 288 districts in 60 provinces around Thailand were recorded using national outbreak data. For the kernel smoothing, the provinces with the highest risk were Phitsanulok, Phichit, Suphan Buri, Ang Thong, Samut Prakan, Bangkok, Chon Buri, Kamphaeng Phet and Saraburi. Kulldorff’s spatial scan statistics showed that the high-risk districts were in the central and lower northern parts of Thailand. The ﬁ ndings conﬁ rmed that central Thailand had the highest risk for HPAI H5N1 outbreaks. The appropriate authorities should focus on this area for disease control and prevention, and should pay special attention to this area when outbreaks occur in neighboring countries. This may help authorities to prevent outbreaks or decrease the magnitude of outbreaks when they occur.